Preparation method of biomedical material with degradable metal skeleton reinforced Zn powder metallurgy with large-area galvanic corrosion structure

By introducing a degradable metal framework with a large-area galvanic corroded structure into zinc alloys, combined with powder metallurgy technology, the problem of slow degradation rate of zinc alloys is solved, and efficient degradation of materials is achieved, excellent biocompatibility and mechanical properties of materials are achieved. .

CN116275055BActive Publication Date: 2025-02-18STOMATOLOGICAL HOSPITAL AFFILIATED TO WENZHOU MEDICAL UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202310320357.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-24
Publication Date
2025-02-18
Estimated Expiration
2043-03-24

AI Technical Summary

Technical Problem

The degradation rate of existing zinc alloys in in vitro immersion experiments and in vivo degradation is less than 0.1mm/y, which cannot meet the degradation rate requirements of bone implants, resulting in stress shielding effect between the implant and the bone tissue, which in turn causes bone atrophy and The sequelae of implant loosening.

Method used

The preparation method of Zn powder metallurgy biomedical materials using a large-area galvanic corrosive structure is used to enhance the preparation method of Zn powder metallurgy biomedical materials. By combining foam metal with pure zinc or zinc alloy powder, powder metallurgy technology is used to form a large number of interfaces during the blank pressing process, promoting The formation of galvanic corrosive structures accelerates the degradation of materials.

Benefits of technology

The high degradation rate of the material is achieved, reaching 316μm/y, close to the bone healing cycle, and has excellent mechanical properties, cytocompatibility and antibacterial properties, meeting the requirement of clinical hemolysis rate below 5%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116275055B_ABST
    Figure CN116275055B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of biomedical metals, and particularly relates to a method for preparing a biomedical material of a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure, comprising a metal skeleton and Zn metal powder, wherein the metal skeleton is one of foamed pure Cu, Fe, and Mg metals, and the Zn metal powder is pure zinc and Zn-Mg, Zn-Cu, Zn-Ca, Zn-Sr, Zn-Se, Zn-RE, Zn-Mn, Zn-Ge, Zn-Li, and Zn-Fe atomized or ball-milled powder. The beneficial effect of the present invention is that the biomedical material of a biomedical material of a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure has relatively excellent mechanical properties while taking into account excellent cell compatibility and antibacterial properties, and can meet the requirement that the clinical hemolysis rate is less than 5%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of biomedical metals, and in particular to a method for preparing a biomedical material with a degradable metal skeleton reinforced with Zn powder metallurgy and a large-area galvanic corrosion structure. Background Art

[0002] Zinc, as an essential element for the human body, acts as a cofactor in certain enzymes and regulatory proteins. Due to its good biocompatibility and degradability, zinc has been proposed as a promising biodegradable material for orthopedic implants. However, the mechanical properties of cast pure zinc and its alloys are too poor to be suitable for orthopedic applications, especially for bone screws and Kirschner wires as load-bearing bone implants. At present, the mechanical properties of alloys are mainly improved by increasing the lattice dislocation density through alloying and providing more dislocation slip systems, and most alloys have a faster degradation rate than pure zinc. However, the degradation rate of most zinc alloys in in vitro immersion tests and in vivo degradation is less than 0.1 mm / y, which is significantly lower than the 0.5 mm / y required for the degradation rate of bone implants. Due to the difference in elastic modulus between the implant and the bone implant, this is bound to increase the stress shielding effect between the implant and the bone tissue when serving in the body, which in turn causes serious sequelae such as bone atrophy and even implant loosening, requiring secondary surgery for repair or removal. Therefore, further accelerating the degradation rate of zinc alloys and maintaining good biocompatibility and mechanical properties have become the main problems to be solved at present.

[0003] Two or more metals with different potentials in a conductive medium will form a corrosion galvanic cell, thus forming galvanic corrosion. Galvanic corrosion can induce and accelerate other types of local corrosion such as stress corrosion, pitting corrosion, crevice corrosion, etc., thereby accelerating corrosion damage. Due to its three-dimensional network structure, high porosity and large specific surface area, foamed metal can form a large-area galvanic corrosion structure with pure zinc to greatly accelerate the corrosion of the implant. At the same time, foamed metal with high mechanical properties can be used as a reinforcing phase in pure zinc to play a role in network pinning reinforcement. On the other hand, due to the large interface between powders, powder metallurgy has more interface area relative to alloy samples, and it is easier to form a galvanic corrosion structure with the matrix, thereby further accelerating the corrosion of the sample. More importantly, the powder metallurgy method has simple equipment during the pressing process, and no or little subsequent mechanical processing is required, which can greatly save metal and reduce product costs. Therefore, combining powder metallurgy technology with foamed metal is a new method to solve the problem of too slow degradation rate of zinc alloy.

[0004] At present, there is no report in domestic and foreign literature on the preparation of degradable metal skeleton / Zn powder metallurgy biomedical materials and the research on corresponding properties. Therefore, it is proposed to use degradable metal skeleton / Zn powder metallurgy biomedical materials as the next stage of degradable biomedical materials. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a degradable metal skeleton reinforced Zn powder metallurgy biomedical material with a large-area galvanic corrosion structure to solve the above problems.

[0006] The technical solution of the present invention is achieved as follows: a method for preparing a degradable metal skeleton reinforced Zn powder metallurgy biomedical material with a large-area galvanic corrosion structure, comprising a metal skeleton and Zn metal powder, wherein the metal skeleton is one of foamed pure Cu, Fe, and Mg metals, and the Zn metal powder is pure zinc and Zn-Mg, Zn-Cu, Zn-Ca, Zn-Sr, Zn-Se, Zn-RE, Zn-Mn, Zn-Ge, Zn-Li, and Zn-Fe atomized or ball-milled powder.

[0007] Furthermore, a method for preparing a biomedical material of a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure comprises the following preparation steps:

[0008] Step 1: First, use wire cutting to cut the foamed pure Fe with a porosity of 10-100 ppi and a thickness of 5-20 mm into a cylinder with a diameter of 40 mm (for extrusion deformation) or a rectangle with a length of 60 mm × 15 mm (width) × 10 mm (height) (for rolling deformation);

[0009] Step 2: Use 30g / L NaOH solution to remove oil under ultrasonic for 10 minutes, then put it into a vacuum oven heated to 60°C for drying for 2 hours;

[0010] Step 3, take out the foamed pure Fe and place it horizontally in a 40mm diameter cylindrical or 60mm (length) × 15mm (width) × 10mm (height) rectangular cold isostatic pressing mold;

[0011] Step 4: filling atomized or ball-milled pure Zn or Zn alloy powder with a particle size of 1 to 10 μm into the pores of the foamed pure Fe, and using a vibration table to perform high-frequency vibration on the cold isostatic pressing mold for 5 to 30 minutes;

[0012] Step 5: cold-press the cold isostatic pressing mold at a pressure of 2 to 40 MPa using a powder tablet press and hold the pressure for 5 to 30 minutes to finally obtain a cylindrical or rectangular powder metallurgy Zn / Fe composite material green body;

[0013] Step 6: After taking the mold, the composite green body is placed in a conventional muffle furnace heated to 250-350° C. for pre-sintering for 0.5-3 hours to obtain a Zn / Fe composite powder metallurgy part;

[0014] Step 7: The cylindrical and rectangular powder metallurgy parts are hot extruded and hot rolled using a 300-ton extruder and a twin-roll mill, respectively.

[0015] Furthermore, in step seven, the hot extrusion process is:

[0016] a. Place the cylindrical powder metallurgy part in a muffle furnace heated to 280-350°C and keep it warm for 0.5-1 hour;

[0017] b. Then quickly put it into an extrusion barrel with a diameter of 40 mm and extrude it at a speed of 0.2 to 10 mm / s to finally obtain a round rod with a diameter of 8 to 10 mm.

[0018] 9. Further, in step seven, the hot rolling process is:

[0019] c. After the rectangular powder metallurgy part is tightly inserted into a 2mm thick pure copper ferrule of the same height as the metallurgical part, it is placed in a muffle furnace heated to 280-350℃ and kept warm for 0.5-1 hour;

[0020] d. After being quickly taken out, hot rolling is performed with a reduction of 5% per pass, and finally foils and plates with a thickness of 0.2 to 2 mm and a total rolling reduction of 80 to 99.8% are obtained.

[0021] Furthermore, in step d, after the first rolling, the heat preservation time before each subsequent rolling is 2 to 5 minutes.

[0022] Furthermore, in step 2, the foamed pure Fe is degreased in an ultrasonic cleaning device.

[0023] Further, the ultrasonic cleaning device comprises:

[0024] A box body, wherein the upper end of the box body is open;

[0025] The ultrasonic generating device is fixedly installed on the left and right side walls of the box;

[0026] A liquid storage cavity is provided on the inner side of the lower end of the box body;

[0027] Limit rods, two limit rods are provided, the two limit rods are fixedly installed on the front side of the box body and are arranged vertically at intervals, and a slide groove is provided along the length direction of the limit rods on the adjacent sides of the two limit rods;

[0028] The sliding member is in an inverted "U" shape, and the two sides of the sliding member are respectively slidably connected in the sliding grooves of the two limit rods;

[0029] The material receiving trough is located in the box body, a support plate is provided below the material receiving trough, and a spring is fixedly installed between the support plate and the lower end surface of the material receiving trough;

[0030] Vertical rods, two vertical rods are provided, the two vertical rods are fixedly installed at the bottom of the box body and are relatively arranged on the left and right sides of the material receiving trough;

[0031] Among them, a nozzle is embedded in the upper edge of the inner side of the box body, and the nozzle of the nozzle is arranged toward the material receiving trough. The liquid storage chamber is provided with a pump body for conveying the stored liquid to the nozzle. The vertical rod is embedded with a plurality of first magnetic blocks arranged at equal distances along its height direction. The first magnetic blocks between the two vertical rods are staggered. Second magnetic blocks are embedded in the upper edges of the left and right sides of the material receiving trough. The box body is also provided with a driving device for driving the sliding part to reciprocate up and down.

[0032] Furthermore, the driving device comprises:

[0033] The drive motor is fixedly mounted on one side of the box body, and the output shaft of the drive motor passes through the outside of the box body and extends between the two side walls of the sliding member;

[0034] A rotating wheel is located between the inner side walls of the sliding member and is key-connected to the output shaft of the driving motor;

[0035] A first tooth, wherein a plurality of the first teeth are provided, and the plurality of first teeth are integrally formed on the left inner wall of the sliding member along the height direction of the sliding member;

[0036] Among them, a second tooth corresponding to the first tooth is integrally formed on the right inner wall of the sliding part, and a plurality of third teeth are arranged on the outer half circumference of the rotating wheel, and the number of teeth of the first tooth, the second tooth and the third tooth is equal.

[0037] The beneficial effects of the present invention are:

[0038] 1. Powder metallurgy has more interface area than alloy samples, and is more likely to form a galvanic corrosion structure with the substrate, thereby further accelerating the corrosion of the sample;

[0039] 2. The biodegradable metal skeleton reinforced Zn powder metallurgy biomedical material with large-area galvanic corrosion structure has excellent mechanical properties while taking into account excellent cell compatibility and antibacterial properties, and can meet the clinical requirement of hemolysis rate below 5%.

[0040] 3. The powder metallurgy method has simple equipment during the pressing process and requires little or no subsequent machining, which can greatly save metal and reduce product costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0042] Figure 1 The SEM image and EDS surface scanning analysis image of the hot extruded Zn / Fe round rod sample of the specific embodiment of the present invention;

[0043] Figure 2 This is a polarization curve diagram of a hot extruded Zn / Fe round rod sample in Hanks' solution in a specific embodiment of the present invention;

[0044] Figure 3 The mechanical properties of hot extruded Zn / Fe round rod specimens after tensile and compression tests according to a specific embodiment of the present invention are shown.

[0045] Figure 4 The electrochemical performance parameters of the hot extruded Zn / Fe round rod sample are fitted after the polarization test in the specific implementation mode of the present invention.

[0046] Figure 5 It is a schematic structural diagram of an ultrasonic cleaning device according to a specific embodiment of the present invention. DETAILED DESCRIPTION

[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention. In the description of this application, it should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The techniques, methods and devices known to ordinary technicians in the relevant fields may not be discussed in detail, but in appropriate cases, the techniques, methods and devices should be regarded as part of the authorization specification. In all examples shown and discussed here, any specific value should be interpreted as merely exemplary, not as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in subsequent drawings.

[0048] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present application can be implemented in an order other than those illustrated or described herein, and the objects distinguished by "first", "second", etc. are generally of one type, and the number of objects is not limited. For example, the first object can be one or more. In addition, "and / or" in the specification and claims represents at least one of the connected objects, and the character " / " generally indicates that the objects associated with each other are in an "or" relationship.

[0049] It should be noted that, in the description of the present application, the orientation or positional relationship indicated by terms such as "front, back, up, down, left, right", "lateral, vertical, perpendicular, horizontal" and "top, bottom" are usually based on the orientation or positional relationship shown in the drawings, and are only for the convenience of describing the present application and simplifying the description. Unless otherwise stated, these orientation words do not indicate or imply that the device or element referred to must have a specific orientation or be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the scope of protection of the present application; the orientation words "inside and outside" refer to the inside and outside relative to the contour of each component itself.

[0050] It should be noted that, in the present application, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, an element defined by the sentence "comprises one..." does not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be noted that the scope of the method and device in the embodiment of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.

[0051] Embodiment 1:

[0052] First, a cylindrical sample with a diameter of 40 mm was cut from pure Fe foam with a porosity of 50 ppi and a thickness of 20 mm by wire cutting, and then degreased with 30 g / L NaOH solution under ultrasonic conditions for 10 minutes and placed in a vacuum furnace heated to 60 ° C for drying for 2 hours. Then, the pure Fe foam was taken out and placed horizontally in a cylindrical cold isostatic pressing mold with a diameter of 40 mm. Atomized pure Zn powder with a particle size of 3 μm was filled into the pores of pure Fe foam, and the cold isostatic pressing mold was vibrated at high frequency for 10 minutes using a vibration table to ensure that the powder fully filled the mold to reduce the generation of pores and the upper layer of powder was flush with the pure Fe foam. The cold isostatic pressing mold was cold pressed and held at a pressure of 30 MPa using a powder tablet press for 20 minutes to finally obtain a cylindrical powder metallurgy Zn / Fe composite green body. After taking the mold, the composite green body was placed in a conventional muffle furnace heated to 300 ° C for pre-sintering for 2 hours to obtain a Zn / Fe composite powder metallurgy part. Finally, the cylindrical powder metallurgy parts were hot extruded using a 300-ton extruder. The hot extrusion process is as follows: the cylindrical powder metallurgy parts were placed in a muffle furnace heated to 320°C for 0.5 hours, and then quickly placed in an extrusion barrel with a diameter of 40 mm, and extruded at 1 mm / s to finally obtain a hot extruded Zn / Fe round bar with a diameter of 10 mm.

[0053] Implementation effect:

[0054] The hot extruded Zn / Fe round bar sample contains pure Fe metal skeleton and Zn matrix. There is a 9.8μm transition layer with high O content between the pure Fe metal skeleton and the Zn matrix, and no obvious peeling occurs, showing good bonding performance. The pure Fe metal skeleton is evenly distributed in the horizontal direction, forming a uniformly distributed lamellar heterogeneous metal structure with the Zn matrix; the tensile strength of the hot extruded Zn / Fe round bar sample is 303.6MPa, the yield strength is 223.7MPa, the elongation is 19.6%, the compressive yield strength is 337.6MPa, and the compressive strain is ≥70%; the corrosion potential, corrosion current density and corrosion rate of the hot extruded Zn / Fe round bar sample obtained by polarization test in Hanks' solution are -1.29V, 0.24A / cm 2, 3.6mm / y. After immersion in Hanks' solution for 90 days, the degradation rate of the hot extruded Zn / Fe round rod sample was 316μm / y, which was close to the bone healing cycle; in Hanks' solution, due to the corrosion potential difference between Fe and Zn, the lamellar structure accelerated the corrosion process as a galvanic corrosion structure; the hemolysis rate of the hot extruded Zn / Fe round rod sample in mouse blood was 2.2%, which met the requirement of clinical medical materials with a hemolysis rate of less than 5%, showing good blood compatibility. After 3 days of culture in the 100%, 50% and 25% concentrations of the hot extruded Zn / Fe round rod sample extract, the cell survival rates were 27.3%, 75.6% and 98.5%, respectively, and the diluted extract showed good cell compatibility. The size of the inhibition zone of the hot extruded Zn / Fe round rod sample after co-culture with Staphylococcus aureus for 1 day was 4.8mm.

[0055] Embodiment 2:

[0056] First, a rectangular sample of 60 mm long × 15 mm wide × 10 mm high was cut from pure Fe foam with a porosity of 50 ppi and a thickness of 20 mm by wire cutting, and then degreased by ultrasonic treatment with 30 g / L NaOH solution for 10 minutes and placed in a vacuum furnace heated to 60 ° C for drying for 2 hours. Then, the pure Fe foam was taken out and placed horizontally in a rectangular cold isostatic pressing mold of 60 mm long × 15 mm wide × 10 mm high. The ball-milled Zn-2Mg alloy powder with a particle size of 10 μm was filled into the pores of the pure Fe foam, and the cold isostatic pressing mold was vibrated at high frequency for 20 minutes using a vibration table to ensure that the powder fully filled the mold to reduce the generation of pores and the height of the upper layer of powder was flush with the pure Fe foam. The cold isostatic pressing mold was cold pressed and pressed for 20 minutes at a pressure of 35 MPa using a powder tablet press, and finally a rectangular powder metallurgy Zn-Mg / Fe composite green body was obtained. After taking out the mold, the composite green body is placed in a conventional muffle furnace heated to 320°C for pre-sintering for 3 hours to obtain a Zn-Mg / Fe composite powder metallurgy part. Finally, the rectangular powder metallurgy part is hot-rolled using a double-roll mill. The hot rolling process is as follows: after the rectangular powder metallurgy part is tightly stuffed into a 2mm thick pure copper ferrule of the same height as the metallurgical part, it is placed in a muffle furnace heated to 320°C and kept warm for 0.5 hours, and then quickly taken out and hot rolled with a 5% reduction per pass. After that, the insulation time before each rolling pass is 5 minutes, and finally a hot-rolled Zn-Mg / Fe plate with a thickness of 2mm and a total rolling reduction of 80% is obtained.

[0057] Implementation effect:

[0058] The tensile strength of the hot-rolled Zn-Mg / Fe plate sample is 346.9MPa, the yield strength is 258.6MPa, the elongation is 16.5%, the compressive yield strength is 365.5MPa, and the compressive strain is 63%; the corrosion potential, corrosion current density and corrosion rate of the hot-rolled Zn-Mg / Fe plate sample obtained by polarization test in Hanks' solution are -1.03V, 0.29A / cm 2 , 4.4mm / y. After immersion in Hanks' solution for 90 days, the degradation rate of the hot-rolled Zn-Mg / Fe plate sample was 359μm / y, which was close to the bone healing cycle; in Hanks' solution, due to the corrosion potential difference between Fe, Mg and Zn, the lamellar structure accelerated the corrosion process as a galvanic corrosion structure; the hemolysis rate of the hot-rolled Zn-Mg / Fe plate sample extract in mouse blood was 3.3%, which met the requirement of clinical medical materials with a hemolysis rate of less than 5%, showing good blood compatibility. After 3 days of culture in the extract of the hot-rolled Zn-Mg / Fe plate sample at 100%, 50% and 25% concentrations, the cell survival rates of MG-63 osteosarcoma cells were 33.6%, 82.6% and 100.2%, respectively, and the diluted extract showed good cell compatibility. The size of the inhibition zone of the hot-rolled Zn-Mg / Fe plate sample after co-culture with Staphylococcus aureus for 1 day was 5.6mm.

[0059] Embodiment 3:

[0060] Further, the ultrasonic cleaning device comprises:

[0061] A box body 1, wherein the upper end of the box body 1 is open;

[0062] The ultrasonic generating device 2 is fixedly mounted on the left and right side walls of the box body 1;

[0063] The liquid storage chamber 3 is opened on the inner side of the lower end of the box body 1;

[0064] Limit rods 4, two limit rods 4 are provided, the two limit rods 4 are fixedly installed on the front side of the box body 1 and are arranged vertically at intervals, and a slide groove arranged along the length direction of the limit rods 4 is provided on the adjacent side of the two limit rods 4;

[0065] The sliding member 5 is in an inverted "U" shape, and the two sides of the sliding member 5 are respectively slidably connected to the sliding grooves of the two limit rods 4;

[0066] A material receiving groove 6 is located in the box body 1, a support plate 7 is provided below the material receiving groove 6, and a spring is fixedly installed between the support plate 7 and the lower end surface of the material receiving groove 6;

[0067] Vertical rods 8, two vertical rods 8 are provided, and the two vertical rods 8 are fixedly installed at the bottom of the box body 1 and are relatively arranged on the left and right sides of the receiving groove 6;

[0068] Among them, a nozzle is embedded in the upper edge of the inner side of the box body 1, and the nozzle of the nozzle is arranged toward the material receiving groove 6. The liquid storage chamber 3 is provided with a pump body for conveying the stored liquid to the nozzle. The vertical rod 8 is embedded with a plurality of first magnetic blocks 9 arranged at equal distances along its height direction. The first magnetic blocks 9 between the two vertical rods 8 are staggered. Second magnetic blocks 91 are embedded in the upper edges of the left and right sides of the material receiving groove 6. The box body 1 is also provided with a driving device for driving the sliding member 5 to reciprocate up and down.

[0069] By adopting the above technical scheme, the driving device can drive the material receiving trough to reciprocate up and down through the sliding part. While moving, through the adsorption effect of the first magnetic block and the second magnetic block and the spring, the material receiving trough can be reciprocated up and down while shaking slightly left and right, which can effectively improve the cleaning and oil removal effect of the material in the trough. After cleaning, the material can be rinsed again through the nozzle to avoid residue. The structure is simple and the use effect is good.

[0070] Embodiment 4:

[0071] Furthermore, the driving device comprises:

[0072] The driving motor is fixedly mounted on one side outside the box body 1, and the output shaft of the driving motor passes through the outside of the box body 1 and extends to between the two side walls inside the sliding member 5;

[0073] The rotating wheel 10 is located between the inner side walls of the sliding member 5 and is key-connected to the output shaft of the driving motor;

[0074] A first tooth 11, wherein a plurality of the first teeth 11 are provided, and the plurality of first teeth 11 are integrally formed on the left inner wall of the sliding member 5 along the height direction of the sliding member 5;

[0075] Among them, a second tooth 12 corresponding to the first tooth 11 is integrally formed on the right inner wall of the sliding member 5, and a plurality of third teeth 13 are provided on the outer half circumference of the rotating wheel 10, and the number of teeth of the first tooth 11, the second tooth 12 and the third tooth 13 are equal.

[0076] By adopting the above technical solution, the third tooth cooperates with the first tooth and the second tooth respectively, and the drive motor only needs to rotate in one direction to complete the operation of driving the sliding member to reciprocate up and down, without the need for frequent reversing, which effectively reduces the load of the drive motor.

[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a biomedical material with a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure, characterized in that: It includes a metal skeleton and Zn metal powder, wherein the metal skeleton is one of foamed pure Cu, Fe, and Mg metals, and the Zn metal powder is pure zinc and atomized or ball-milled powder of Zn-Mg, Zn-Cu, Zn-Ca, Zn-Sr, Zn-Se, Zn-RE, Zn-Mn, Zn-Ge, Zn-Li, and Zn-Fe; The preparation method comprises the following preparation steps: Step 1: First, use wire cutting to cut the foamed pure Fe with a porosity of 10-100 ppi and a thickness of 5-20 mm into a cylinder with a diameter of 40 mm for extrusion deformation or a rectangle with a length of 60 mm × a width of 15 mm × a height of 10 mm for rolling deformation; Step 2: Use 30g / L NaOH solution to remove oil under ultrasonic for 10 minutes and then put it into a vacuum oven heated to 60°C for drying for 2 hours; Step 3, take out the foamed pure Fe and place it horizontally in a 40mm diameter cylindrical or 60mm long × 15mm wide × 10mm high rectangular cold isostatic pressing mold; Step 4: Fill the pores of the foamed pure Fe with atomized or ball-milled pure Zn or Zn alloy powder with a particle size of 1 to 10 μm, and use a vibration table to perform high-frequency vibration on the cold isostatic pressing mold for 5 to 30 minutes; Step 5: cold-press the cold isostatic pressing mold at a pressure of 2 to 40 MPa using a powder tablet press and hold the pressure for 5 to 30 minutes to finally obtain a cylindrical or rectangular powder metallurgy Zn / Fe composite material green body; Step 6: After taking out the mold, the composite green body is placed in a conventional muffle furnace heated to 250-350° C. for pre-sintering for 0.5-3 hours to obtain a Zn / Fe composite powder metallurgy part; Step 7: hot extrusion and hot rolling of cylindrical and rectangular powder metallurgy parts using a 300-ton extruder and a twin-roll mill, respectively; In step seven, the hot extrusion process is: a. Place the cylindrical powder metallurgy part in a muffle furnace heated to 280-350℃ and keep it warm for 0.5-1 hour; b. Then quickly put it into an extrusion barrel with a diameter of 40mm and extrude it at 0.2-10mm / s to finally obtain a round rod with a diameter of 8-10mm; In step seven, the hot rolling process is: c. After tightly inserting the rectangular powder metallurgy part into a 2mm thick pure copper ferrule of the same height as the metallurgy part, put it into a muffle furnace heated to 280-350℃ and keep it warm for 0.5-1 hour; d. After being quickly taken out, hot rolling is performed with a reduction of 5% per pass, and finally a foil and plate with a thickness of 0.2 to 2 mm and a total rolling reduction of 80 to 99.8% is obtained; In step d, after the first rolling, the heat preservation time before each subsequent rolling is 2 to 5 minutes.

2. The method for preparing a biomedical material with a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure according to claim 1, characterized in that: In step 2, the foamed pure Fe is degreased in an ultrasonic cleaning device.

3. The method for preparing a biomedical material with a degradable metal skeleton reinforced Zn powder metallurgy with a large-area galvanic corrosion structure according to claim 2, characterized in that: The ultrasonic cleaning device includes: A box body (1), the upper end of which is open; an ultrasonic generating device (2), which is fixedly mounted on the left and right side walls of the box body (1); A liquid storage chamber (3) is provided on the inner side of the lower end of the box body (1); Limit rods (4), two limit rods (4) are provided, the two limit rods (4) are fixedly installed on the front side of the box body (1) and are arranged vertically at intervals, and a sliding groove arranged along the length direction of the limit rods (4) is provided on adjacent sides of the two limit rods (4); The sliding member (5) is in an inverted "U" shape, and two sides of the sliding member (5) are respectively slidably connected to the sliding grooves of the two limit rods (4); A material receiving trough (6) is located in the box body (1), a support plate (7) is provided below the material receiving trough (6), and a spring is fixedly installed between the support plate (7) and the lower end surface of the material receiving trough (6); A vertical rod (8), wherein two vertical rods (8) are provided, and the two vertical rods (8) are fixedly installed on the bottom of the box body (1) and are arranged on the left and right sides of the material receiving trough (6) opposite to each other; A nozzle is embedded in the inner upper edge of the box body (1), and the nozzle of the nozzle is arranged toward the material receiving groove (6). The liquid storage chamber (3) is provided with a pump body for conveying the stored liquid to the nozzle. The vertical rod (8) is embedded with a plurality of first magnetic blocks (9) arranged at equal intervals along its height direction. The first magnetic blocks (9) between the two vertical rods (8) are arranged in a staggered manner. Second magnetic blocks (91) are embedded in the upper edges of the left and right sides of the material receiving groove (6). The box body (1) is also provided with a driving device for driving the sliding member (5) to reciprocate up and down.

4. The method for preparing a biomedical material with a large-area galvanic corrosion structure and a degradable metal skeleton reinforced Zn powder metallurgy is characterized by: The drive unit includes: A drive motor is fixedly mounted on one side outside the box (1), and an output shaft of the drive motor passes through the outside of the box (1) and extends between two side walls inside the sliding member (5); A rotating wheel (10) is located between two side walls of the sliding member (5) and is key-connected to the output shaft of the driving motor; A first tooth (11), wherein a plurality of the first teeth (11) are provided, and the plurality of first teeth (11) are integrally formed on the inner left side wall of the sliding member (5) along the height direction of the sliding member (5); A second tooth (12) corresponding to the first tooth (11) is integrally formed on the right inner wall of the sliding member (5), and a plurality of third teeth (13) are provided on the outer half circumference of the rotating wheel (10), and the number of teeth of the first tooth (11), the second tooth (12) and the third tooth (13) is equal.

Citation Information

Patent Citations

  • Efficient fruit cleaning device

    CN107212440A

  • Preparation method of biomedical degradable metal framework reinforced Zn-based composite material with large-area galvanic corrosion structure

    CN114042898A

  • Chinese herbal medicine cleaning device with high cleaning efficiency

    CN212944248U

  • Throwing type ultrasonic mold cleaning machine

    CN214184347U